Copper and palladium-catalyzed sequential reactions: one-pot synthesis of isoindolo[2, 1-b]isoquinolin-7(5H)-ones. Issue 17 (10th April 2019) - Saini, Hitesh Kumar; Dhiman, Shiv; Nandwana, Nitesh Kumar; Krishnan, Rangan; Kumar, Anil
Abstract : A highly efficient protocol has been developed for the synthesis of diversely substituted isoindolo[2, 1- b ]isoquinolin-7(5 H )-ones through sequential Cu(ii )-catalyzed Sonogashira coupling, intramolecular hydroamidation followed by palladium-catalyzed ligand free Heck reaction. Abstract : A highly efficient protocol has been developed for the synthesis of diversely substituted isoindolo[2, 1- b ]isoquinolin-7(5 H )-ones through sequential Cu(ii )-catalyzed Sonogashira coupling, intramolecular hydroamidation followed by palladium-catalyzed ligand-free Heck reaction. Good to excellent yields (41–94%) were observed with excellent substrate scope and functional group tolerance. The developed method represents a practical strategy for the construction of bioactive isoindolo[2, 1- b ]isoquinolin-7(5 H )-ones.